A BETTER LOOK AT THE STUDENTS’ READING INTEREST AND THEIR READING COMPREHENSION - Devistha Arry Purnama; Dewi Warna; Eka Sartika (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2023)
The purpose of this study was to find out whether or not there is a correlation and the impact between students’ reading interest and students’ reading comprehension at SMA Negeri 9 Palembang. This research applied quantitative study with correlational design method to answer the objective of the research. Researchers used convenience sampling to determine the sample. The members of the sample in this research were 207 students. The data of this research were collected by using two instruments. The data were collected by using a questionnaire for students’ reading interest and a test for reading comprehension. The researchers used SPSS to analyze the data. The researchers used Pearson Product Moment correlation and regression analysis to find out the answers of the research questions. Based on the results of Pearson Product Moment found that r is 0.419. It indicates the moderate correlation between variable X and variable Y and students’ reading interest influences reading comprehension. It is found that the value of R square was 0.175. It can be concluded that the students’ reading interest contributed 17.5% to their students’ reading comprehension achievement. It can be said that the better the students’ interest in reading, the better the score will be.